(untitled) (Journal of Contemporary Philology, 2025)
Macedonian’s tripartite article system (proximal, neutral, and distal) aligns with similar systems found in other Balkan Slavic varieties, but also exhibits parallels with non-Slavic languages, such as Wolof, which feature deictic definite articles. This paper investigates the morphosyntactic and semantic features of these articles in Balkan Slavic, aiming to clarify their status within the broader typology of definiteness and deixis. We show through the study of the Macedonian spoken corpus that there are significant differences between the articles regarding their relative frequency. Cross-linguistic comparison further informs the typological status of these articles. In both Balkan Slavic and Atlantic languages like Wolof, definite articles are enclitics, with one form generally occurring significantly more frequently than the others. While interesting secondary functions such as nominal tense have been proposed for these articles, these features are not diagnostic of their “articlehood” and may be expressed by demonstrative pronouns in other languages.